2017
DOI: 10.1177/0305735617689953
|View full text |Cite
|
Sign up to set email alerts
|

Effects of preferred relaxing music after acute stress exposure: A randomized controlled trial

Abstract: In daily contexts, coping with stressful events involves a great level of personal resources to recover baseline conditions efficiently, a process called stress recovery. The aim of this study was to assess the effects of an intervention based on preferred relaxing music on the recovery after stress exposure. We also analyzed the effect of gender on stress recovery. Fifty-eight undergraduates underwent a paradigm of laboratory-based stress induction and were randomly assigned to either the control or the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 77 publications
1
27
1
Order By: Relevance
“…Stress nowadays is very common, so much so that it has become one of the major problems of today’s society [ 1 ]. The phenomenon of chronic stress is affecting more people every year [ 2 ]. Brain–computer interface technology can be a helpful tool in the fight against stress.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stress nowadays is very common, so much so that it has become one of the major problems of today’s society [ 1 ]. The phenomenon of chronic stress is affecting more people every year [ 2 ]. Brain–computer interface technology can be a helpful tool in the fight against stress.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common bases for this state, the so-called stressors, are moments which require acting under pressure and are observed primarily in interpersonal contacts, the workplace and situations associated with finances [ 1 ]. Therefore, stress is generated through animbalance between environmental requirements and an individual’s perception of their skills which are insufficient to satisfy those requirements [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…This can be achieved by meeting thresholds on peak signal values at Fp1 and Fp2. The study participants were allowed to bring music files of their own choice [60]. The trigger for audio was the play and pause.…”
Section: A Neurofeedback Stimulus Contentsmentioning
confidence: 99%
“…The trigger for audio was the play and pause. In the case of video, the study participants were given the freedom to bring video files of their own choice [60]. During the neurofeedback session, the triggers for the video was also play and pause.…”
Section: A Neurofeedback Stimulus Contentsmentioning
confidence: 99%
“…Personalised music is defined as: 'music that has been integrated into a person's life and is based on personal preference' (Gerdner 2012). Several studies have illustrated the therapeutic benefits of personalised music, including a reduction in agitation, stress responses and anxiety, and improved mood and patient and staff engagement (Sung et al 2010;Martin et al 2016;Park et al 2016;de la Torre-Luque et al 2017). A Cochrane systematic review published in 2017 reported that 17 randomised control trials found music-based interventions for people living with dementia had little or no effect on improving emotional wellbeing, behavioural problems or cognitive abilities.…”
Section: Introductionmentioning
confidence: 99%